2007
DOI: 10.1534/genetics.106.067801
|View full text |Cite
|
Sign up to set email alerts
|

Brc1-Mediated Rescue of Smc5/6 Deficiency: Requirement for Multiple Nucleases and a Novel Rad18 Function

Abstract: Smc5/6 is a structural maintenance of chromosomes complex, related to the cohesin and condensin complexes. Recent studies implicate Smc5/6 as being essential for homologous recombination. Each gene is essential, but hypomorphic alleles are defective in the repair of a diverse array of lesions. A particular allele of smc6 (smc6-74) is suppressed by overexpression of Brc1, a six-BRCT domain protein that is required for DNA repair during S-phase. This suppression requires the postreplication repair (PRR) protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 54 publications
6
69
0
Order By: Relevance
“…28,45,46 These similarities strengthen the connections between Brc1 and the Smc5/6 holocomplex, of which Brc1 was initially discovered as a high-copy suppressor of the smc6-74 hypomorphic allele. 19,20 Brc1 localization in pericentromeric heterochromatin largely depends on the interaction of its C-terminal BRCT domains with γH2A-marked chromatin, although, as we have discovered, the requirement for this interaction for TBZ resistance only becomes obvious when the phosphorylation of histone H2A by Bub1 kinase is also ablated. 28 The new findings reported in this study indicate that the structural integrity of the N-terminal BRCT domains is also important for its functions in replication stress responses and resistance to TBZ (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…28,45,46 These similarities strengthen the connections between Brc1 and the Smc5/6 holocomplex, of which Brc1 was initially discovered as a high-copy suppressor of the smc6-74 hypomorphic allele. 19,20 Brc1 localization in pericentromeric heterochromatin largely depends on the interaction of its C-terminal BRCT domains with γH2A-marked chromatin, although, as we have discovered, the requirement for this interaction for TBZ resistance only becomes obvious when the phosphorylation of histone H2A by Bub1 kinase is also ablated. 28 The new findings reported in this study indicate that the structural integrity of the N-terminal BRCT domains is also important for its functions in replication stress responses and resistance to TBZ (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Earlier studies suggested that the sensitivity to DNA damaging agents in brc1Δ cells was likely caused by a DNA repair defect, which was consistent with the genetic interactions involving Brc1 and the Smc5/6 holocomplex. [19][20][21] However, a recent study indicated that the requirement for Brc1 more likely involves a role in the resumption of DNA replication at stalled or damaged replication forks. 22 In the case of collapsed replication forks, resumption of DNA replication absolutely depends on homology directed repair.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…Genetic epistasis analysis of the suppression of smc6-74 by Brc1 indicates that Brc1 functions in conjunction with the PRR proteins Rhp18 and the TLS polymerases, with the HR machinery, and with multiple structure-specific nucleases (Lee et al, 2007;Sheedy et al, 2005). All of these genes are notable for their function in the processing of stalled and/or collapsed replication forks.…”
Section: Introductionmentioning
confidence: 99%
“…Brc1 was initially identified as a high-copy suppressor of smc6-74 (Verkade et al 1999), which encodes a subunit of the essential ''structural maintenance of chromosomes'' Smc5/6 complex that functions in chromosome organization and DNA repair (Lehmann et al 1995;McDonald et al 2003;Harvey et al 2004;Pebernard et al 2004Pebernard et al , 2006. The Brc1-mediated rescue of smc6-74 is thought to proceed via a novel Rhp18-dependent mechanism, utilizing multiple nucleases to facilitate the initial cleavage of abnormal structures that arise due to compromised Smc5/6 function and their subsequent processing by HR (Sheedy et al 2005;Lee et al 2007). Loss of Brc1 function results in sensitivity to a range of DNA-damaging drugs that generate lesions specifically during S-phase or impede DNA replication (Verkade et al 1999;Sheedy et al 2005).…”
mentioning
confidence: 99%